Peningkatan Hasil Belajar Matematika dengan metode MEA pada Kelas X di MA Darussalam Manuju Kabupaten Gowa - Azwan Anwar; Anriani Anriani; Rahmah Mustafa; Nur Aisyah; Nursamsi Nursamsi (Transformasi Masyarakat : Jurnal Inovasi Sosial dan Pengabdian, 2025)
This service aims to explain the increase in mathematics learning outcomes when implementing the MEA method in class X at MA Darussalam Manuju. The data collection technique uses data about students' mathematics learning completeness obtained from the results of mathematics learning tests carried out at the end of each cycle, with 27 class X students as the subject. The instrument is a learning results test sheet. The results show that the application of the MEA method can improve students' mathematics learning outcomes. This can be proven based on the average score of student learning outcomes in cycle I reaching an average of 69.3703 and in cycle II reaching an average of 87. Based on the learning outcome completeness category used, the score for students' mathematics learning outcomes categorized as complete in cycle I was 81.48% and in cycle II it increased to 100%. These results can be concluded that there has been an increase in Mathematics Learning outcomes using the Means Ends Analysis Method.